Post-pandemic face-to-face learning environments for undergraduate students: A scoping review protocol. - Karim Garzon Diaz; Angy Villamil Duarte; Sandra Velasco Forero; Sandra Herrera Jacobo (PLoS ONE)
Objective This scoping review explores the existing literature related to post-pandemic face-to-face learning environments for undergraduate students following their participation in virtual classes during the Covid-19 pandemic. The secondary objectives are focused to identify the cognitive; emotional, or communicative demands that characterize students; changes in pedagogical strategies; and primary recommendations regarding post-pandemic face-to-face education in the context of Covid-19. Introduction The global emergency created by the presence of COVID-19 has led to significant change in the daily lives of people worldwide, ranging from lockdowns to the proliferation of virtual channels for social interaction and learning. Interest in its effects remains relevant in various fields including social, economic, health, technological, and educational studies. The transition back to face-to-face studies in university settings requires new adjustment processes for both students and teachers, necessitating pedagogical transformations and addressing cognitive, emotional, communicative, and habituation demands. Studies on the return to face-to-face studies in university settings are relatively scarce and warrant in-depth research. Inclusion criteria This review will include studies completed and published in calendar years 2022 and 2024 that involve post-pandemic face-to-face learning environments for undergraduate students from any geographical area. Methodology This scoping review will follow the JBI methodology for conducting scoping reviews. The following databases will be used: Academic Search Complete, Inter-American Development Bank, CLACSO, and The UNESCO Institute for Higher Education in Latin America and the Caribbean (IESALC), Dimensions, DOAB, DOAJ, ERIC, LILACS, Psicodoc, Redalyc, Redib, Scielo, Scopus, Dialnet, Web Of Science, Latindex, Google Scholar, SocArXiv. The search will aim to locate publications without language restrictions from any geographic location, including peer-reviewed articles, grey literature, preprints, technical notes, and policy reports. Three independent reviewers will screen, retrieve and review full-text studies and extract data. Consensus will be sought in the event of disagreement. The search results will be presented in the PRISMA-ScR flowchart. A narrative summary will also be included (Tricco AC 2018). Trial registration Registration of systematic reviews: Open Science Framework (https://doi.org/10.17605/OSF.IO/6P9QB).